Can we abandon foregut exclusion for an ideal and safe metabolic surgery? - Widjaja, Jason; Chu, Yuxiao; Yang, Jianjun; Wang, Jian; Gu, Yan (Frontiers in Endocrinology, 2022)
Foregut (foregut exclusions) and hindgut (rapid transit of nutrients to the distal intestine) theories are the most commonly used explanations for the metabolic improvements observed after metabolic surgeries. However, several procedures that do not comprise duodenal exclusions, such as sleeve with jejunojejunal bypass, ileal interposition, and transit bipartition and sleeve gastrectomy were found to have similar diabetes remission rates when compared with duodenal exclusion procedures, such as gastric bypass, biliopancreatic diversion with duodenal switch, and diverted sleeve with ileal interposition. Moreover, the complete exclusion of the proximal intestine could result in the malabsorption of several important micronutrients. This article reviews commonly performed procedures, with and without foregut exclusion, to better comprehend whether there is a critical need to include foregut exclusion in metabolic surgery.